2019
DOI: 10.3390/ma12030531
|View full text |Cite
|
Sign up to set email alerts
|

The Penetration Ability of Calcium Silicate Root Canal Sealers into Dentinal Tubules Compared to Conventional Resin-Based Sealer: A Confocal Laser Scanning Microscopy Study

Abstract: The purpose of this study was to compare the penetration ability of calcium silicate root canal sealers and conventional resin-based sealer using confocal laser scanning microscopy (CLSM). A total of 60 recently extracted single-rooted human premolars were used in this study. The root canals were prepared to a size 40/0.06 taper with ProFile rotary instruments and irrigated with NaOCl and EDTA. After drying all canals, the specimens were randomly divided into three experimental groups (n = 20): Group 1, gutta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 35 publications
(42 reference statements)
3
27
0
2
Order By: Relevance
“…On the other hand, McMichael et al [ 42 ] also found lower percentage values in resin-based materials when compared to silicate-based materials using single-cone technique, but the results for resin-based materials were superior when using continuous wave technique. The results from the study performed by Kim et al [ 18 ] are also consistent with these findings. In the present study, the single-cone technique was used as a standardized obturation technique for all of the sealer samples, aiming to avoid the influence of the differences in obturation technique on the results.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…On the other hand, McMichael et al [ 42 ] also found lower percentage values in resin-based materials when compared to silicate-based materials using single-cone technique, but the results for resin-based materials were superior when using continuous wave technique. The results from the study performed by Kim et al [ 18 ] are also consistent with these findings. In the present study, the single-cone technique was used as a standardized obturation technique for all of the sealer samples, aiming to avoid the influence of the differences in obturation technique on the results.…”
Section: Discussionsupporting
confidence: 84%
“…Dentine tubular penetration represents a physical barrier for microorganisms and increases the retention of the sealer [ 17 , 18 ], hence, the importance of its assessment in these new materials. Among the factors that determine the tubular penetration of root canal sealers, the consistency and fluidity are two relevant parameters to be considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After canal obturation with each sealer, roots are embedded in a self-cure resin and sectioned perpendicular to the long axis of the root. Then, CLSM is used to evaluate the patterns or depth of dentin-penetrating sealer [ 35 ]. In the evaluation of dye leakage, each root is immersed in freshly prepared 1% methylene blue dye for 72 hours after canal obturation.…”
Section: Reviewmentioning
confidence: 99%
“…The most commonly used sealers are calcium hydroxide sealers, glass ionomer sealers, zinc oxide eugenol sealers, resin-based sealers, and the recently introduced calcium silicate-based sealers. AH Plus Plus (Dentsply DeTrey GmbH, Konstanz, Germany) is a conventional epoxy resin-based root canal sealer with low microleakage and good penetration ability into dentinal walls [8,9]. This sealer exhibits toxicity when freshly mixed that gradually reduces upon setting [7,10].…”
Section: Introductionmentioning
confidence: 99%